Language Politics and Fiqh’s Authority on Qur'anic Reinterpretation in Indonesian Translation Practices - Muhammad Ulul Albab Musaffa (Al-Mazaahib, 2025)
The book Qur'an Translation in Indonesia: Scriptural Politics in a Multilingual State edited by Johanna Pink offers an interdisciplinary analysis of Qur'anic translation practices in Indonesia within the framework of language politics, religious authority, and the articulation of Islamic law (fiqh). Through a variety of historical and contemporary case studies, the book highlights how Qur'ānic translations serve not only as educative tools, but also as instruments of legal orthodoxy through state intervention, school of thought preferences and local dynamics. The review focuses on the aspects of Islamic law that emerge in the choice of diction, the influence of schools of fiqh, and the relationship between tafsir, fatwa, and translation-based legal products. It is concluded that Qur'an translation in Indonesia is a semi-normative practice that is loaded with ideological, legal, and political content, and has a significant impact on the construction of Islamic understanding in contemporary Indonesian Muslim society.